Risk management assessment based on managerial communication skills for libyan oil and gas projects - Mohamed Omar, Elkbuli (2024)
The project management community is actively debating how to identify the factors that lead to project success. The project manager’s position and its impact on the project’s overall outcomes have become a hot topic among researchers, practitioners, and academics. Attempts to define the traits and competencies of good project managers have led to the recognition that a range of competencies beyond just technical skills is required. Because a project manager’s human and leadership skills are critical to a project’s success, these abilities must be taught and developed as part of project management education. In response to this demand, this study aims to identify factors affecting managerial communication skills in Libya’s oil and gas projects and an approach for implementing risk management principles in these projects to improve their efficiency. A review of relevant literature and the administration of a questionnaire were used to determine factors impacting risk management implementation related to managerial communication skills. To achieve a good response rate, 260 questionnaires were randomly sent to oil and gas companies in Tripoli, Libya. A total of 246 usable questionnaires were received, which was sufficient for analysis using structural equation modeling (SEM) in Smart PLS software. Additionally, a structural equation modeling approach was employed to examine the direct and moderating relationships proposed by the hypotheses. Because the quantitative research design was based on the positivist research paradigm, the methodology was created to focus on the research questions and the study's objectives. The questionnaire was created using a closed interval measurement scale, and great attention was given to designing all the survey instruments. The findings of this study, obtained through SEM, suggest that managerial soft skills can improve continuous risk management processes and intra-project communication in Libya's oil and gas industry. It is anticipated that this approach will assist project stakeholders during the planning phase and aid in producing high-quality projects that are closely monitored in terms of both time and cost management. This suggests that the study's findings contribute to a better understanding of the factors affecting risk management related to managerial communication skills. They might be implemented to assist managers' decision-making processes and serve as a valuable reference for subsequent research in the field of construction project management.